Diversifying food and diets : using agricultural biodiversity to improve nutrition and health - Fanzo, Jessica; Hunter, Danny; Borelli, Teresa; Mattei, Federico (Issues in agricultural biodiversity., 2013)
"This book aims to explore what the current state of knowledge is on the role of agricultural biodiversity in improving nutrition and food security. The book will examine and challenge some of the prevailing myths and assumptions to improving nutrition through agriculture mechanisms so as to identify the key research and implementation gaps"--